Ownership structure and corporate social responsibility disclosure: some Malaysian evidence - Mohd Ghazali, Nazli Anum (Emerald Group Publishing, 2007)
Purpose – The purpose of this article is to examine the influence of ownership structure on corporate social responsibility (CSR) disclosure in Malaysian company annual reports (CARs). Design/methodology/approach – The study uses a CSR disclosure checklist to measure the extent of CSR disclosure in annual reports and a multiple regression analysis to examine the association between ownership structure and the extent of CSR disclosure in annual reports. Findings – The paper finds that, even among the larger and actively traded stocks in Malaysia, there is considerable variability in the amount of social activities disclosed in corporate annual reports. Results from multiple regression analysis show that, consistent with expectations, companies in which the directors hold a higher proportion of equity shares (owner-managed companies) disclosed significantly less CSR information, while companies in which the government is a substantial shareholder disclosed significantly more CSR information in their annual reports. Research limitations/implications – The sample for this study comes from larger and actively traded stocks on the Bursa Malaysia. Thus, the results may not be generalizable to smaller and less actively traded stocks. Practical implications – The findings appear to suggest that the level of CSR disclosure in annual reports of companies depends on the extent of ‘‘public pressure’’ faced by each company. The results also raise the question of whether corporate involvement in social activities should be made a mandatory disclosure in annual reports to better assess the extent of ‘‘corporate citizenship’’ of Malaysian companies. Originality/value – The study finds that ownership structure, which had been ignored in prior studies on factors influencing CSR disclosure,has an impact on CSR disclosure.